Graphene-filled nylon high-thermal-conductivity composite material and preparation method thereof
By using phosphorus-nitrogen quaternary ammonium polyamide modified graphene in nylon 6, the problems of low thermal conductivity and poor interfacial compatibility of nylon 6 were solved, and the preparation of nylon composite materials with high thermal conductivity and flame retardancy was achieved, and the expansion of its Application scope.
Patent Information
- Application Number
- CN202411509853.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-18
AI Technical Summary
Nylon 6 material has low thermal conductivity and poor interface compatibility with graphene, resulting in uneven dispersion of fillers and inability to form good thermal conductivity paths, limiting its application in the electronics industry.
By adding phosphorus-nitrogen quaternary ammonium polyamide to nylon 6, the graphene is modified by electrostatic action and hydroxyl and carboxyl groups to generate non-covalent bonding, improving the interface compatibility between graphene and nylon 6, and through melt blending method and extrusion molding process to prepare highly thermally conductive nylon composite materials.
It significantly improves the thermal conductivity and flame retardant properties of nylon materials, forms a more complete thermal conductivity path, enhances the mechanical properties of the materials, and broadens its application range in the electronics industry.
Smart Images

Figure BDA0005105147220000051 
Figure BDA0005105147220000052
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a graphene-filled nylon high thermal conductivity composite material and a preparation method thereof. Background Art
[0002] With the rapid development of the electronics industry, higher requirements are placed on various heat dissipation materials; traditional thermal conductive materials are generally based on metals and their oxides and nitrides, and these materials have many shortcomings such as difficulty in processing and molding, poor solvent resistance and poor mechanical properties, which limit their application in related fields; nylon is one of the widely used engineering plastics, with high fatigue strength and rigidity, good heat resistance, low friction coefficient, good wear resistance, and excellent comprehensive performance. It is widely used in machinery, electronics, automobiles, aviation and other fields, but due to its low thermal conductivity, relatively poor strength and flame retardancy, it cannot meet the development requirements of modern industry; therefore, the development of new thermal conductive composite materials with nylon as the matrix has certain theoretical and practical application value.
[0003] Nylon 6 is a thermal insulator. Long-term use will cause the material temperature to rise, which will affect the life of electronic devices. Currently, high-addition thermal conductive fillers such as alumina and silicon nitride are usually used to modify the thermal conductivity of nylon 6, but this will also lose other properties of nylon, such as mechanical properties and durability. Graphene is made of sp 2 Hybridized carbon atoms are closely arranged to form a unique two-dimensional periodic honeycomb lattice structure. The stable carbon hexagonal rings in its structural units give it excellent thermal properties, and it is considered to be an excellent thermal control material. Adding graphene to nylon can greatly improve thermal conductivity. High thermal conductivity plastics with graphene as filler can meet the requirements of thermal management and high-density and high-integration assembly development in the electronics industry.
[0004] By adding graphene filler to the nylon matrix, the thermal conductivity of the nylon material can be significantly improved. However, the interface compatibility of graphene and nylon materials is poor, the dispersion performance is poor, and it is easy to produce agglomeration, and a good thermal conductivity path cannot be formed. In the prior art, the modification is generally carried out by melt blending, that is, the polymer is first melted at a high temperature, and then the filler is added, and the filler is dispersed in the polymer material by the shearing action of the screw. Finally, the composite material is obtained by extrusion molding and other processes. It is economical and practical, but there is a problem of poor filler dispersion uniformity.
[0005] Nylon, like most polymer materials, is a material with good electrical insulation properties and is prone to electrostatic accidents. At the same time, due to its flammable properties, its application in specific fields is also limited. Therefore, the present invention aims to synthesize a polyamide containing phosphorus and nitrogen flame retardant elements that has good compatibility with nylon 6 to modify graphene, and adopt a melt blending method, through extrusion granulation and injection molding, to obtain a high thermal conductive nylon composite material. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a graphene-filled nylon high thermal conductivity composite material and a preparation method thereof, so as to improve the dispersibility of graphene in nylon 6, further improve the thermal conductivity and flame retardant properties of the nylon material, and broaden its application range.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] A method for preparing a graphene-filled nylon high thermal conductivity composite material comprises the following steps:
[0009] Step (1): Weigh graphene oxide and place it in a sodium hydroxide aqueous solution, stir it into a suspension, add quaternary ammonium polyamide of phosphorus nitrogen, react in a constant temperature oscillator at 60-80° C. for 1-3 hours, filter and wash with deionized water, and check the filtrate with 0.1M silver nitrate solution until there is no precipitate. After the solid is dried, phosphorus nitrogen polyamide modified graphene is obtained.
[0010] Step (2): vacuum drying the nylon 6 slices at 110-125° C. for 2-5 h, placing them in a high-speed mixer with graphene oxide and phosphorus nitrogen polyamide modified graphene, mixing them evenly at a speed of 1000-1500 r / min, placing them in a twin-screw extruder, granulating them by melt extrusion, and finally injection molding them in an injection molding machine at an injection molding temperature of 240-270° C. and an injection molding pressure of 70-90 MPa to obtain a graphene-filled nylon high thermal conductivity composite material.
[0011] Preferably, the molar concentration of the sodium hydroxide aqueous solution in step (1) is 0.03-0.06 mol / L.
[0012] Preferably, in step (1), the ratio of graphene oxide to phosphorus nitrogen quaternary ammonium salt polyamide is 100 g:(3-15) g.
[0013] Preferably, in step (2), the ratio of nylon 6 chips, graphene oxide, and phosphorus nitrogen polyamide modified graphene is 100g:(5-10)g:(0.5-2.5)g.
[0014] Preferably, the process parameters of the twin-screw extruder in step (2) are: zone 1 temperature 190-200°C, zone 2 temperature 220-230°C, zone 3 temperature 235-245°C, zone 4 temperature 230-240°C, zone 5 temperature 215-225°C, die head temperature 230-240°C, main engine speed 250-280r / min, and feeding speed 35-50r / min.
[0015] Preferably, the preparation method of the phosphorus nitrogen quaternary ammonium salt polyamide in step (1) comprises the following steps:
[0016] Step S1: Under a nitrogen atmosphere, add 2,4-dichloro-1,3,5-triazine and acetonitrile to a reaction flask, stir evenly, then add 4-(dimethylamino)butyric acid, stir to react, and after the reaction is completed, cool to room temperature, filter, wash with deionized water, and dry to obtain a triazine quaternary ammonium salt diacid monomer.
[0017] Step S2: under a nitrogen atmosphere, add triazine quaternary ammonium salt diacid monomer, bis(p-aminophenyl) phosphate and N-methylpyrrolidone into a reaction flask, mix well, add pyridine and triphenyl phosphite, stir to dissolve, react at 100-120°C for 12-24h, after the reaction is completed, pour the reaction solution into deionized water, precipitate, filter, wash with ethanol, and dry to obtain phosphorus nitrogen quaternary ammonium salt polyamide.
[0018] Preferably, in step S1, the ratio of 2,4-dichloro-1,3,5-triazine to 4-(dimethylamino)butyric acid is 1 mol:(2.05-2.2) mol.
[0019] Preferably, in step S1, the reaction temperature is 75-90° C. and the reaction time is 16-32 h.
[0020] Preferably, in step S2, the ratio of triazine quaternary ammonium salt diacid monomer, bis(p-aminophenyl) phosphate, pyridine, and triphenyl phosphite is 1 mol: (1.02-1.1) mol: (0.02-0.05) mol: (0.005-0.01) mol.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The invention firstly carries out quaternization reaction on 2,4-dichloro-1,3,5-triazine and 4-(dimethylamino)butyric acid to obtain triazine quaternary ammonium salt diacid monomer, then carries out polycondensation reaction with bis(p-aminophenyl) phosphate to obtain phosphorus nitrogen quaternary ammonium salt polyamide, then generates electrostatic action with active groups on the surface of graphene oxide to obtain phosphorus nitrogen polyamide modified graphene, finally melt-blended with nylon 6 slices, extruded and formed, to obtain graphene filled nylon high thermal conductivity composite material.
[0023] The structure of the phosphorus nitrogen quaternary ammonium salt polyamide contains a quaternary ammonium salt structure, which can produce non-covalent bonds with the carboxyl and hydroxyl groups of graphene oxide through electrostatic action to achieve grafting modification with graphene; the phosphorus nitrogen polyamide modified graphene is filled into the nylon 6 matrix as a filler, wherein the polyamide has a similarity with the structure of nylon 6, which improves the interface compatibility between the two, and overlaps the graphene sheets together, so that the heat conduction path constructed by the graphene filler in the nylon 6 matrix is more complete and the heat conduction is more continuous; as the filling amount continues to increase, the conduction of thermal energy is converted from the conduction mode of filler-matrix-filler to filler-filler, avoiding the problem of low heat transfer coefficient of nylon 6 matrix and greatly improving the thermal conductivity of the composite material.
[0024] Phosphorus-nitrogen polyamide modified graphene contains triazine groups and phosphoric acid structures. The nitrogen-containing compounds produced by the decomposition of the triazine structure at high temperature can promote the carbonization of nylon 6, have a high coverage rate on the combustion zone, and play a role in heat insulation, oxygen isolation, and preventing combustion; the phosphoric acid structure forms polyphosphoric acid when heated, which can act as an acid source and promote carbonization, thereby improving the flame retardant properties of the composite material; when the graphene filler is very evenly dispersed in the nylon 6 matrix and has a strong interface bonding force with the matrix, the graphene sheet can prevent the material from being deformed by external force, play a role in skeleton support, and thus improve the mechanical properties of the composite material. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Preparation of graphene oxide: Using the improved Hummers method, 1.2g of sodium nitrate was added to 46mL of concentrated sulfuric acid, 1.0g of flake graphite was added thereto, and stirred until uniformly mixed, then stirred in an ice-water bath and 6.0g of potassium permanganate was slowly added. The system was then heated to 40°C, stirred for 6-8h, and then slowly and continuously added while the system was heated to 70°C, reacted for 30min, 100mL of deionized water and 10mL of hydrogen peroxide were added, and the reaction was stopped after 5-15min, the reaction solution was filtered while hot, the filter cake was taken out and ultrasonically dispersed in deionized water, washed and filtered with 5% HCl solution and deionized water, and dried to obtain graphene oxide.
[0027] Bis(p-aminophenyl)phosphate, CAS number is 407578-85-2.
[0028] 2,4-Dichloro-1,3,5-triazine, CAS number: 2831-66-5
[0029] 4-(Dimethylamino)butyric acid, CAS number is 693-11-8.
[0030] Nylon 6 chips, commercially available industrial grade, from Zhuzhou Chemical Technology Research Institute.
[0031] Example 1
[0032] (1) Under a nitrogen atmosphere, 35 mmol of 2,4-dichloro-1,3,5-triazine and 280 mL of acetonitrile were added to a reaction flask, stirred evenly, and then 75.6 mmol of 4-(dimethylamino)butyric acid was added. The mixture was reacted at 85° C. for 24 h, cooled to room temperature, filtered, washed with deionized water, and dried to obtain a triazine quaternary ammonium salt diacid monomer. 1 H NMR hydrogen spectrum (300 Hz, DMSO): 2.01 (m, 4H), 2.30 (m, 4H), 2.90 (s, 12H), 3.22 (m, 4H), 9.68 (s, 1H), 12.01 (s, 2H). The preparation reaction formula is as follows:
[0033]
[0034] (2) Under nitrogen atmosphere, 32 mmol of triazine quaternary ammonium salt diacid monomer, 33.6 mmol of bis(p-aminophenyl) phosphate and 800 mL of N-methylpyrrolidone were added to the reaction flask, and after mixing, 1.12 mmol of pyridine and 0.24 mmol of triphenyl phosphite were added, and after stirring and dissolving, the mixture was reacted at 110° C. for 16 h. After the reaction was completed, the reaction solution was poured into deionized water, and the precipitate was precipitated, filtered, washed with ethanol, and dried to obtain phosphorus nitrogen quaternary ammonium salt polyamide. The preparation reaction formula is as follows:
[0035]
[0036] (3) Weigh 10 g of graphene oxide and place it in a sodium hydroxide aqueous solution with a molar concentration of 0.05 mol / L, stir it to form a suspension, add 0.3 g of phosphazenium quaternary ammonium polyamide, react in a constant temperature oscillator at 70° C. for 2 h, filter and wash with deionized water, and check the filtrate with 0.1 M silver nitrate solution until there is no precipitate. After the solid is dried, the phosphazenium polyamide modified graphene is obtained.
[0037] (4) 100 g of nylon 6 slices were vacuum dried at 120 ° C for 5 h, and then placed in a high-speed mixer with 8 g of graphene oxide and 0.5 g of phosphorus nitrogen polyamide modified graphene, mixed evenly at a speed of 1200 r / min, placed in a twin-screw extruder, and granulated by melt extrusion. The process parameters of the twin-screw extruder were as follows: zone 1 temperature 195 ° C, zone 2 temperature 225 ° C, zone 3 temperature 240 ° C, zone 4 temperature 235 ° C, zone 5 temperature 220 ° C, head temperature 235 ° C, main engine speed 260 r / min, feeding speed 45 r / min, and finally injection molding in an injection molding machine, the injection molding temperature was 260 ° C, and the injection molding pressure was 80 MPa to obtain a graphene-filled nylon high thermal conductivity composite material.
[0038] Example 2
[0039] (1) Under a nitrogen atmosphere, 80 mmol of 2,4-dichloro-1,3,5-triazine and 400 mL of acetonitrile were added to a reaction flask, stirred evenly, and then 164 mmol of 4-(dimethylamino)butyric acid was added. The mixture was reacted at 90° C. for 16 h, cooled to room temperature, filtered, washed with deionized water, and dried to obtain a triazine quaternary ammonium salt diacid monomer. 1 H NMR (300 Hz, DMSO): 2.01 (m, 4H), 2.30 (m, 4H), 2.90 (s, 12H), 3.22 (m, 4H), 9.68 (s, 1H), 12.01 (s, 2H).
[0040] (2) Under a nitrogen atmosphere, 75 mmol of triazine quaternary ammonium salt diacid monomer, 76.5 mmol of bis(p-aminophenyl) phosphate and 1950 mL of N-methylpyrrolidone were added to a reaction flask, and after mixing evenly, 2.7 mmol of pyridine and 0.375 mmol of triphenyl phosphite were added, and after stirring to dissolve, the mixture was reacted at 120° C. for 12 h. After the reaction was completed, the reaction solution was poured into deionized water, the precipitate was filtrated, washed with ethanol, and dried to obtain phosphorus nitrogen quaternary ammonium salt polyamide.
[0041] (3) Weigh 10 g of graphene oxide and place it in a sodium hydroxide aqueous solution with a molar concentration of 0.03 mol / L, stir it to form a suspension, add 0.6 g of phosphazene quaternary ammonium polyamide, react in a constant temperature oscillator at 80° C. for 1 h, filter and wash with deionized water, check the filtrate with 0.1 M silver nitrate solution until there is no precipitate, and dry the solid to obtain phosphazene polyamide modified graphene.
[0042] (4) 100 g of nylon 6 slices were vacuum dried at 125°C for 2 h, then placed in a high-speed mixer with 5 g of graphene oxide and 1 g of phosphorus nitrogen polyamide modified graphene, mixed evenly at a speed of 1500 r / min, placed in a twin-screw extruder, and granulated by melt extrusion. The process parameters of the twin-screw extruder were as follows: zone 1 temperature 200°C, zone 2 temperature 230°C, zone 3 temperature 245°C, zone 4 temperature 240°C, zone 5 temperature 225°C, head temperature 240°C, main engine speed 280 r / min, feed rate 50 r / min, and finally injection molding in an injection molding machine at an injection molding temperature of 270°C and an injection molding pressure of 90 MPa to obtain a graphene-filled nylon high thermal conductivity composite material.
[0043] Example 3
[0044] (1) Under a nitrogen atmosphere, 30 mmol of 2,4-dichloro-1,3,5-triazine and 300 mL of acetonitrile were added to a reaction flask, and after stirring, 66 mmol of 4-(dimethylamino)butyric acid was added, and the mixture was reacted at 75° C. for 32 h. The mixture was cooled to room temperature, filtered, washed with deionized water, and dried to obtain a triazine quaternary ammonium salt diacid monomer. 1 H NMR (300 Hz, DMSO): 2.01 (m, 4H), 2.30 (m, 4H), 2.90 (s, 12H), 3.22 (m, 4H), 9.68 (s, 1H), 12.01 (s, 2H).
[0045] (2) Under a nitrogen atmosphere, 25 mmol of triazine quaternary ammonium salt diacid monomer, 27.5 mmol of bis(p-aminophenyl) phosphate and 750 mL of N-methylpyrrolidone were added to a reaction flask, and after mixing evenly, 1.25 mmol of pyridine and 0.25 mmol of triphenyl phosphite were added, and after stirring to dissolve, the mixture was reacted at 100° C. for 24 h. After the reaction was completed, the reaction solution was poured into deionized water, the precipitate was precipitated, filtered, washed with ethanol, and dried to obtain phosphorus nitrogen quaternary ammonium salt polyamide.
[0046] (3) Weigh 10 g of graphene oxide and place it in a sodium hydroxide aqueous solution with a molar concentration of 0.06 mol / L, stir it to form a suspension, add 0.9 g of phosphazene quaternary ammonium salt polyamide, react in a constant temperature oscillator at 60° C. for 3 h, filter and wash with deionized water, and check the filtrate with 0.1 M silver nitrate solution until there is no precipitate. After the solid is dried, the phosphazene polyamide modified graphene is obtained.
[0047] (4) 100 g of nylon 6 slices were vacuum dried at 110°C for 5 h, and then placed in a high-speed mixer with 10 g of graphene oxide and 1.5 g of phosphorus nitrogen polyamide modified graphene, mixed evenly at a speed of 1000 r / min, placed in a twin-screw extruder, and granulated by melt extrusion. The process parameters of the twin-screw extruder were as follows: zone 1 temperature 190°C, zone 2 temperature 220°C, zone 3 temperature 235°C, zone 4 temperature 230°C, zone 5 temperature 215°C, head temperature 230°C, main engine speed 250 r / min, feed rate 35 r / min, and finally injection molding in an injection molding machine at an injection molding temperature of 240°C and an injection molding pressure of 70 MPa to obtain a graphene-filled nylon high thermal conductivity composite material.
[0048] Example 4
[0049] (1) Under a nitrogen atmosphere, 50 mmol of 2,4-dichloro-1,3,5-triazine and 375 mL of acetonitrile were added to a reaction flask, stirred evenly, and then 106 mmol of 4-(dimethylamino)butyric acid was added. The mixture was reacted at 80° C. for 30 h, cooled to room temperature, filtered, washed with deionized water, and dried to obtain a triazine quaternary ammonium salt diacid monomer. 1 H NMR (300 Hz, DMSO): 2.01 (m, 4H), 2.30 (m, 4H), 2.90 (s, 12H), 3.22 (m, 4H), 9.68 (s, 1H), 12.01 (s, 2H).
[0050] (2) Under a nitrogen atmosphere, 45 mmol of triazine quaternary ammonium salt diacid monomer, 45.9 mmol of bis(p-aminophenyl) phosphate and 1170 mL of N-methylpyrrolidone were added to a reaction flask, and after mixing evenly, 1.45 mmol of pyridine and 0.27 mmol of triphenyl phosphite were added, and after stirring to dissolve, the mixture was reacted at 115° C. for 15 h. After the reaction was completed, the reaction solution was poured into deionized water, the precipitate was filtrated, washed with ethanol, and dried to obtain phosphorus nitrogen quaternary ammonium salt polyamide.
[0051] (3) Weigh 10 g of graphene oxide and place it in a sodium hydroxide aqueous solution with a molar concentration of 0.045 mol / L, stir it to form a suspension, add 1.2 g of phosphazenium quaternary ammonium polyamide, react in a constant temperature oscillator at 75° C. for 2 h, filter and wash with deionized water, and check the filtrate with 0.1 M silver nitrate solution until there is no precipitate. After the solid is dried, the phosphazenium polyamide modified graphene is obtained.
[0052] (4) 100 g of nylon 6 slices were vacuum dried at 120 ° C for 5 h, and then placed in a high-speed mixer with 8 g of graphene oxide and 2 g of phosphorus nitrogen polyamide modified graphene, mixed evenly at a speed of 1350 r / min, placed in a twin-screw extruder, and granulated by melt extrusion. The process parameters of the twin-screw extruder were as follows: zone 1 temperature 195 ° C, zone 2 temperature 220 ° C, zone 3 temperature 240 ° C, zone 4 temperature 235 ° C, zone 5 temperature 220 ° C, head temperature 240 ° C, main engine speed 270 r / min, feeding speed 40 r / min, and finally injection molding in an injection molding machine, the injection molding temperature was 260 ° C, and the injection molding pressure was 85 MPa to obtain a graphene-filled nylon high thermal conductivity composite material.
[0053] Example 5
[0054] (1) Under a nitrogen atmosphere, 60 mmol of 2,4-dichloro-1,3,5-triazine and 375 mL of acetonitrile were added to a reaction flask, stirred evenly, and then 129.5 mmol of 4-(dimethylamino)butyric acid was added. The mixture was reacted at 90° C. for 24 h, cooled to room temperature, filtered, washed with deionized water, and dried to obtain a triazine quaternary ammonium salt diacid monomer. 1 H NMR (300 Hz, DMSO): 2.01 (m, 4H), 2.30 (m, 4H), 2.90 (s, 12H), 3.22 (m, 4H), 9.68 (s, 1H), 12.01 (s, 2H).
[0055] (2) Under a nitrogen atmosphere, 45 mmol of triazine quaternary ammonium salt diacid monomer, 48.6 mmol of bis(p-aminophenyl) phosphate and 1150 mL of N-methylpyrrolidone were added to a reaction flask, and after mixing evenly, 1.45 mmol of pyridine and 0.28 mmol of triphenyl phosphite were added, and after stirring to dissolve, the mixture was reacted at 105° C. for 16 h. After the reaction was completed, the reaction solution was poured into deionized water, the precipitate was precipitated, filtered, washed with ethanol, and dried to obtain phosphorus nitrogen quaternary ammonium salt polyamide.
[0056] (3) Weigh 10 g of graphene oxide and place it in a sodium hydroxide aqueous solution with a molar concentration of 0.05 mol / L, stir it to form a suspension, add 1.5 g of quaternary ammonium polyamide of phosphorus nitrogen, react in a constant temperature oscillator at 80° C. for 3 h, filter and wash with deionized water, and check the filtrate with 0.1 M silver nitrate solution until there is no precipitate. After the solid is dried, phosphorus nitrogen polyamide modified graphene is obtained.
[0057] (4) 100 g of nylon 6 slices were vacuum dried at 120°C for 5 h, and then placed in a high-speed mixer with 9 g of graphene oxide and 2.5 g of phosphorus nitrogen polyamide modified graphene, mixed evenly at a speed of 1350 r / min, placed in a twin-screw extruder, and granulated by melt extrusion. The process parameters of the twin-screw extruder were as follows: zone 1 temperature 200°C, zone 2 temperature 230°C, zone 3 temperature 245°C, zone 4 temperature 235°C, zone 5 temperature 220°C, head temperature 240°C, main engine speed 275 r / min, feed rate 40 r / min, and finally injection molding in an injection molding machine at an injection molding temperature of 260°C and an injection molding pressure of 85 MPa to obtain a graphene-filled nylon high thermal conductivity composite material.
[0058] Comparative Example 1
[0059] (1) Under a nitrogen atmosphere, 35 mmol of 2,4-dichloro-1,3,5-triazine and 280 mL of acetonitrile were added to a reaction flask, and after stirring, 75.6 mmol of 4-(methylamino)butyric acid (CAS No. 1119-48-8) was added, and the mixture was reacted at 85° C. for 24 h, cooled to room temperature, filtered, washed with deionized water, and dried to obtain a triazine tertiary amine diacid monomer (structural formula: ). 1 H NMR (300 Hz, DMSO): 1.89 (m, 4H), 2.30 (m, 4H), 3.03 (s, 6H), 3.49 (m, 4H), 7.44 (s, 1H), 12.01 (s, 2H).
[0060] (2) Under a nitrogen atmosphere, 32 mmol of triazine tertiary amine diacid monomer, 33.6 mmol of bis(p-aminophenyl) phosphate and 800 mL of N-methylpyrrolidone were added to a reaction flask, and after mixing evenly, 1.12 mmol of pyridine and 0.24 mmol of triphenyl phosphite were added, and after stirring to dissolve, the mixture was reacted at 110° C. for 16 h. After the reaction was completed, the reaction solution was poured into deionized water, the precipitate was precipitated, filtered, washed with ethanol, and dried to obtain phosphorus nitrogen polyamide.
[0061] (3) 100 g of nylon 6 chips were vacuum dried at 120 °C for 5 h, then placed in a high-speed mixer with 8 g of graphene oxide and 0.5 g of phosphorus nitrogen polyamide, mixed evenly at a speed of 1200 r / min, placed in a twin-screw extruder, and granulated by melt extrusion. The process parameters of the twin-screw extruder were as follows: zone 1 temperature 195 °C, zone 2 temperature 225 °C, zone 3 temperature 240 °C, zone 4 temperature 235 °C, zone 5 temperature 220 °C, head temperature 235 °C, main engine speed 260 r / min, feed rate 45 r / min, and finally injection molding in an injection molding machine at an injection molding temperature of 260 °C and an injection molding pressure of 80 MPa to obtain a graphene-filled nylon composite material.
[0062] Comparative Example 2
[0063] (1) Under a nitrogen atmosphere, 35 mmol of 1,3-dichlorobenzene (CAS No. 541-73-1) and 280 mL of acetonitrile were added to a reaction flask, stirred evenly, and then 75.6 mmol of 4-(dimethylamino)butyric acid was added. The mixture was reacted at 85° C. for 24 h, cooled to room temperature, filtered, washed with deionized water, and dried to obtain a quaternary ammonium salt diacid monomer (structural formula: ). 1 H NMR (300 Hz, DMSO): 2.00 (m, 4H), 2.30 (m, 4H), 3.22 (m, 4H), 3.72 (s, 12H), 6.67 (m, 2H), 6.74 (s, 1H), 7.35 (m, 1H), 12.01 (s, 2H).
[0064] (2) Under a nitrogen atmosphere, 32 mmol of quaternary ammonium salt diacid monomer, 33.6 mmol of 4,4'-diaminobiphenyl (CAS No. 92-87-5) and 800 mL of N-methylpyrrolidone were added to a reaction flask, and after mixing evenly, 1.12 mmol of pyridine and 0.24 mmol of triphenyl phosphite were added, and after stirring to dissolve, the mixture was reacted at 110° C. for 16 h. After the reaction was completed, the reaction solution was poured into deionized water, the precipitate was filtrated, washed with ethanol, and dried to obtain quaternary ammonium salt polyamide.
[0065] (3) Weigh 10 g of graphene oxide and place it in a sodium hydroxide aqueous solution with a molar concentration of 0.05 mol / L, stir it to form a suspension, add 0.3 g of quaternary ammonium salt polyamide, react in a constant temperature oscillator at 70° C. for 2 h, filter and wash with deionized water, and check the filtrate with 0.1 M silver nitrate solution until there is no precipitate. After the solid is dried, polyamide-modified graphene is obtained.
[0066] (4) 100 g of nylon 6 chips were vacuum dried at 120°C for 5 h, then placed in a high-speed mixer with 8 g of graphene oxide and 0.5 g of polyamide-modified graphene, mixed evenly at a speed of 1200 r / min, placed in a twin-screw extruder, and granulated by melt extrusion. The process parameters of the twin-screw extruder were as follows: zone 1 temperature 195°C, zone 2 temperature 225°C, zone 3 temperature 240°C, zone 4 temperature 235°C, zone 5 temperature 220°C, head temperature 235°C, main engine speed 260 r / min, feed rate 45 r / min, and finally injection molding in an injection molding machine at an injection molding temperature of 260°C and an injection molding pressure of 80 MPa to obtain a graphene-filled nylon composite material.
[0067] Comparative Example 3
[0068] 100g nylon 6 slices were vacuum dried at 120°C for 5h, then placed in a high-speed mixer with 8g graphene oxide, mixed evenly at a speed of 1200r / min, placed in a twin-screw extruder, and granulated by melt extrusion. The process parameters of the twin-screw extruder were as follows: zone one temperature of 195°C, zone two temperature of 225°C, zone three temperature of 240°C, zone four temperature of 235°C, zone five temperature of 220°C, head temperature of 235°C, main engine speed of 260r / min, feeding speed of 45r / min, and finally injection molding in an injection molding machine, the injection molding temperature of 260°C, and the injection molding pressure of 80MPa to obtain a graphene-filled nylon composite material.
[0069] Thermal conductivity test: The prepared composite material was pressed into a shape with a size of 40×30×2 mm, polished smooth with sandpaper, and measured with a thermal conductivity tester. Each sample was tested three times and the average value was taken.
[0070] Table 1 Thermal conductivity test
[0071] <![CDATA[Thermal conductivity (W·m -1 ·K -1 )]]> Example 1 0.42 Example 2 0.68 Example 3 0.93 Example 4 1.36 Example 5 1.41 Comparative Example 1 0.35 Comparative Example 2 0.40 Comparative Example 3 0.31
[0072] It can be seen from the test results in the above table that with the increase of the content of phosphorus nitrogen polyamide modified graphene, the thermal conductivity of the composite material gradually increases, wherein the thermal conductivity coefficient in Example 5 is 1.41 W·m -1 ·K -1 , excellent thermal conductivity; this is because the phosphorus nitrogen quaternary ammonium salt polyamide structure contains a quaternary ammonium salt structure, which can produce non-covalent bonds with the carboxyl and hydroxyl groups of graphene oxide through electrostatic action to achieve grafting modification with graphene; the phosphorus nitrogen polyamide modified graphene is filled into the nylon 6 matrix as a filler, wherein the polyamide has a similarity with the nylon 6 structure, which improves the interface compatibility between the two, and overlaps the graphene sheets together, so that the thermal conduction path constructed by the graphene filler in the nylon 6 matrix is more complete, and the heat conduction is more continuous; as the filling amount continues to increase, the conduction of thermal energy is converted from the filler-matrix-filler conduction mode to the filler-filler, avoiding the problem of low heat transfer coefficient of the nylon 6 matrix, and greatly improving the thermal conductivity of the composite material.
[0073] The triazine tertiary amine diacid monomer in Comparative Example 1 does not contain a quaternary ammonium salt structure and cannot produce an electrostatic effect with graphene oxide, resulting in uneven dispersion in the nylon 6 matrix and poor thermal conductivity; Comparative Example 2 contains quaternary ammonium salt cations, which improves the dispersibility of the graphene filler; Comparative Example 3 only adds graphene oxide, which is easy to agglomerate and cannot form an effective thermal conduction path, and has the worst thermal conductivity.
[0074] Limiting oxygen index test: According to the standard GB / T 2406-2009, the limiting oxygen index instrument is used for testing.
[0075] Vertical burning rating test: According to UL-94 standard, the test is carried out using a horizontal-vertical burning tester.
[0076] Table 2 Flame retardant performance test
[0077] Limiting oxygen index (%) Vertical burning rating (UL-94) Example 1 25.5 V-0 Example 2 28.3 V-0 Example 3 30.6 V-0 Example 4 32.1 V-0 Example 5 32.4 V-0 Comparative Example 1 25.2 V-0 Comparative Example 2 22.6 V-2 Comparative Example 3 22.5 V-2
[0078] It can be seen from the test results in the above table that with the increase of the content of phosphorus nitrogen polyamide modified graphene, the flame retardant properties of the composite material are gradually enhanced. The limiting oxygen index in Example 5 is 32.4%, and the vertical combustion grade is V-0, which belongs to the level of flame retardant materials; this is because the phosphorus nitrogen polyamide modified graphene contains triazine groups and phosphoric acid structures. The nitrogen-containing compounds produced by the decomposition of the triazine structure at high temperature can promote the carbonization of nylon 6, and have a high coverage rate on the combustion zone, which plays a role in heat insulation, oxygen isolation, and preventing combustion; the phosphoric acid structure forms polyphosphoric acid when heated, which can act as an acid source and promote carbonization, thereby improving the flame retardant properties of the composite material.
[0079] Tensile strength test: According to the standard GB / T 1040-1992, the tensile performance of the sample was tested using a universal material testing machine at a tensile speed of 10 mm / min.
[0080] Impact resistance test: According to the standard GB / T 1843-2008, the cantilever beam impact machine is used to test the impact performance of the sample, and the sample has no notch.
[0081] Table 3 Mechanical properties test
[0082] Tensile strength(MPa) <![CDATA[Impact strength (kJ / m 2 )]]> Example 1 70.2 5.5 Example 2 78.9 6.3 Example 3 86.2 7.4 Example 4 95.3 8.5 Example 5 96.2 8.6 Comparative Example 1 60.4 4.6 Comparative Example 2 68.1 5.3 Comparative Example 3 55.2 4.1
[0083] When the graphene filler is dispersed very evenly in the nylon 6 matrix and has a strong interfacial bonding force with the matrix, the graphene sheets can prevent the material from deforming due to external forces, play a skeletal support role, and thus improve the mechanical properties of the composite material.
[0084] The above embodiments are only exemplary embodiments of the present invention and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present invention, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.
Claims
1. A method for preparing a graphene-filled nylon high thermal conductivity composite material, characterized in that: The preparation method comprises the following steps: Step (1): weighing graphene oxide and placing it in a sodium hydroxide aqueous solution, stirring to form a suspension, adding phosphorus nitrogen quaternary ammonium polyamide, reacting at 60-80° C. in a constant temperature oscillator for 1-3 hours, filtering and washing with deionized water, and checking the filtrate with a 0.1M silver nitrate solution until there is no precipitate, and drying the solid to obtain phosphorus nitrogen polyamide modified graphene; Step (2): vacuum drying the nylon 6 slices at 110-125° C. for 2-5 h, placing them in a high-speed mixer with graphene oxide and phosphorus nitrogen polyamide modified graphene, mixing them evenly at a speed of 1000-1500 r / min, placing them in a twin-screw extruder, granulating them by melt extrusion, and finally injection molding them in an injection molding machine at an injection molding temperature of 240-270° C. and an injection molding pressure of 70-90 MPa to obtain a graphene-filled nylon high thermal conductivity composite material.
2. The method for preparing the graphene-filled nylon high thermal conductivity composite material according to claim 1, characterized in that: The molar concentration of the sodium hydroxide aqueous solution in step (1) is 0.03-0.06 mol / L.
3. The method for preparing the graphene-filled nylon high thermal conductivity composite material according to claim 1, characterized in that: In the step (1), the ratio of graphene oxide to phosphazene quaternary ammonium salt polyamide is 100 g:(3-15) g.
4. The method for preparing the graphene-filled nylon high thermal conductivity composite material according to claim 1, characterized in that: In the step (2), the ratio of nylon 6 chips, graphene oxide, and phosphorus nitrogen polyamide modified graphene is 100g:(5-10)g:(0.5-2.5)g.
5. The method for preparing the graphene-filled nylon high thermal conductivity composite material according to claim 1, characterized in that: The process parameters of the twin-screw extruder in step (2) are: zone 1 temperature 190-200°C, zone 2 temperature 220-230°C, zone 3 temperature 235-245°C, zone 4 temperature 230-240°C, zone 5 temperature 215-225°C, die head temperature 230-240°C, main engine speed 250-280r / min, and feeding speed 35-50r / min.
6. The method for preparing the graphene-filled nylon high thermal conductivity composite material according to claim 1, characterized in that: The preparation method of the phosphorus nitrogen quaternary ammonium salt polyamide in step (1) comprises the following steps: Step S1: under a nitrogen atmosphere, add 2,4-dichloro-1,3,5-triazine and acetonitrile to a reaction flask, stir evenly, add 4-(dimethylamino)butyric acid, stir to react, and after the reaction is completed, cool to room temperature, filter, wash with deionized water, and dry to obtain a triazine quaternary ammonium salt diacid monomer; Step S2: under a nitrogen atmosphere, add triazine quaternary ammonium salt diacid monomer, bis(p-aminophenyl) phosphate and N-methylpyrrolidone into a reaction flask, mix well, add pyridine and triphenyl phosphite, stir to dissolve, react at 100-120°C for 12-24h, after the reaction is completed, pour the reaction solution into deionized water, precipitate, filter, wash with ethanol, and dry to obtain phosphorus nitrogen quaternary ammonium salt polyamide.
7. The method for preparing the graphene-filled nylon high thermal conductivity composite material according to claim 6, characterized in that: In the step S1, the ratio of 2,4-dichloro-1,3,5-triazine to 4-(dimethylamino)butyric acid is 1 mol:(2.05-2.2) mol.
8. The method for preparing the graphene-filled nylon high thermal conductivity composite material according to claim 6, characterized in that: In step S1, the reaction temperature is 75-90° C. and the reaction time is 16-32 hours.
9. The method for preparing the graphene-filled nylon high thermal conductivity composite material according to claim 6, characterized in that: In the step S2, the ratio of triazine quaternary ammonium salt diacid monomer, bis(p-aminophenyl) phosphate, pyridine and triphenyl phosphite is 1 mol: (1.02-1.1) mol: (0.02-0.05) mol: (0.005-0.01) mol.
10. A graphene-filled nylon high thermal conductivity composite material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Graphene composite modified flame-retardant nylon plastic
CN120865701A